Annual ring width in the arctic-alpine dwarf-shrub species Salix herbacea - Dataset from long-term alpine ecosystem research in central Norway (LTAER-NO) - Kühnapfel, Mira; Albrecht, Eike Corina; Dobbert, Svenja; Pape, Roland; Wundram, Dirk; Löffler, Jörg (ERDKUNDE, 2023)
Here we present a datapaper containing microscopically measured data of annual ring widths in the arctic-alpine dwarf-shrub species Salix herbacea (central Norway). The dataset will be updated with future measurements.